A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes: Heptapteridae) from the Sierra Nevada de Santa Marta, Colombia - Conde-Saldaña, Cristhian C.; Albornoz-Garzón, Juan G.; García-Melo, Jorge E.; Dergam, Jorge A.; Villa-Navarro, Francisco A. (Zootaxa, 2019)
A new species of Pimelodella is described from northern coastal drainages of the Sierra Nevada de Santa Marta (SNSM), Colombia. The new species is diagnosed from all trans-Andean congeners by the following unique combination of characters: head length 22.2–23.7% SL, bony interorbital width 17.6–21.6% HL, maxillary barbels length 53.0–68.3% SL, inner mental-barbels length 14.4–20.0% SL, body width 17.6–21.1% SL, dorsal-fin spine length 8.3–13.7% SL, dorsal-fin base 12.3–14.9% SL, pectoral-fin spine length 12.9-14.5% SL, pectoral-fin spine length without dentations on the distal posterior margin 21.6–29.8% in pectoral-fin spine length, maximum depth of dentations in posterior margin of pectoral-fin spine 1.40–1.68 times in the width of the spine at its base, adipose-fin base length 22.8–26.4% SL, caudal-peduncle depth 9.2–10.5% SL, 40 vertebrae, having a conspicuous paired dark brown stripe on the dorsal surface of body, extending from posterior margin of head to caudal-fin insertion and a wide dark brown midlateral stripe present. The isolated occurrence of this new taxon living in allopatry in coastal drainages of the SNSM could have interesting biogeographic implications for dispersal and vicariance processes of the ichthyofauna from northern South America.